2013
DOI: 10.1016/j.rbmo.2013.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of outcomes after IVF using an aneuploidy risk model derived from time-lapse imaging without PGS

Abstract: Time-lapse imaging of human preimplantation IVF embryos has enabled objective algorithms based on novel observations of development (morphokinetics) to be used for clinical selection of embryos. Embryo aneuploidy, a major cause of IVF failure, has been correlated with specific morphokinetic variables used previously to develop an aneuploidy risk classification model. The purpose of this study was to evaluate the effectiveness and potential impact of this model for unselected IVF patients without biopsy and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
195
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(204 citation statements)
references
References 18 publications
5
195
0
1
Order By: Relevance
“…Such a mechanism could explain our results, but further future studies need to be undertaken to elucidate the molecular nature of the mechanism(s). Campbell et al [20] further depicted no significant differences between aneuploid and euploid embryos in irregular division patterns (Bdirect^or Brapid^division defined as being less than of 5-h duration), which may further support our contention. We additionally studied the implantation rate, clinical pregnancy rate, ongoing pregnancy rate, and live birth rate in the AC 1-3c , AC 2-4c , AC 3-5c , and AC 4-6c groups as illustrated in Table 4.…”
Section: Discussionsupporting
confidence: 78%
“…Such a mechanism could explain our results, but further future studies need to be undertaken to elucidate the molecular nature of the mechanism(s). Campbell et al [20] further depicted no significant differences between aneuploid and euploid embryos in irregular division patterns (Bdirect^or Brapid^division defined as being less than of 5-h duration), which may further support our contention. We additionally studied the implantation rate, clinical pregnancy rate, ongoing pregnancy rate, and live birth rate in the AC 1-3c , AC 2-4c , AC 3-5c , and AC 4-6c groups as illustrated in Table 4.…”
Section: Discussionsupporting
confidence: 78%
“…Recent studies reported information on the association of the type of fertilization [22], the IVF protocol used [23], female obesity [24], and smoking [25] on embryo kinetics and development. Interestingly, the sensitivity and specificity of the modality in terms of predicting the progression to the blastocyst stage was >90 % by measuring parameters at day 2 after fertilization, before embryonic genome activation [26,27], while the bad prognosis of good-performing but unviable embryos reaches a specificity of 100 % [28]; moreover, the area under the receiver operating characteristic curve has been reported to be 0.74 for live birth [29] with high intra-and inter-observer correlation [30].…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies only use light intensity to quantify illumination effect on embryos [3,15,16]. Light at longer wavelength carries lower energy and red light is recommended as a safe illumination source for embryo observation systems [15] and is now routinely applied in timelapse incubation systems [11,12,[19][20][21]. However, the maximum tolerance of embryos to red light is unknown, and no comparisons have yet been made of an eventual effect of maximizing light exposures to obtain even more morphological details over a full pre-implantation period in-vitro, i.e.…”
Section: Introductionmentioning
confidence: 99%